PENGEMBANGAN WEB PEMBELAJARAN FISIKA SEBAGAI SUPLEMEN MATA KULIAH ELEKTRONIKA DASAR 1 - Septiani, Rika; Latifah , Sri; Siregar, Antomi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to determine the feasibility and response to physics learning web as supplement subjects Elektronika Elementary 1 is developed. This research is an R & D research that adopts the development of Borg & Gall. This research data obtained from questionnaire validation of material experts, media experts and IT experts. The type of data produced is qualitative data which is analyzed by guidance criteria of assessment category to determine product quality. The feasibility of web media of physics learning as supplement of Basic Element 1 subjects and response from material expert validator, media expert and IT expert with percentage of assessment result from material expert on average 85,43% in very feasible category, media expert 76,11% in decent category, IT expects 76.66% in the eligible category, the percentage of the results of small group experimental assessment averaged 82.39% in very reasonable categories and field trials of 82.48% in very viable categories. Web learning is already worthy of use as a web of physics learning. ABSTRAKPenelitian ini bertujuan untuk mengetahui kelayakan dan respon terhadap web pembelajaran fisika sebagai suplemen mata kuliah Elektronika Dasar 1 yang dikembangkan. Penelitian ini merupakan penelitian R&D yang mengadopsi pengembangan dari Borg & Gall. Data penelitian ini diperoleh dari angket validasi ahli materi, ahli media dan ahli IT. Jenis data yang dihasilkan adalah data kualitatif yang dianalisis dengan pedoman kriteria kategori penilaian untuk menentukan kualitas produk. Kelayakan media web pembelajaran fisika sebagai suplemen mata kuliah Elektronika Dasar 1 dan respon dari validator ahli materi, ahli media dan ahli IT dengan persentase hasil penilaian dari ahli materi rata-rata 85,43% dalam kategori sangat layak, ahli media 76,11% dalam kategori layak, ahli IT 76,66% dalam kategori layak, persentase hasil penilaian uji coba kelompok kecil rata-rata 82,39% dalam kategori sangat layak dan uji coba lapangan 82,48% dalam kategori sangat layak. Web pembelajaran ini sudah layak digunakan sebagai web pembelajaran fisika.